Research in environmental education and Education for Sustainable Development in Germany: the state of the art - Seybold, Hansjörg; Rieß, Werner (Environmental Education Research, 2006)
This article outlines the state of the art in German research on environmental education and education for sustainable development (ESD). Empirical German research on the importance of environmental education and ESD for schools is analysed in relation to three research fields. First, survey research describes the practice of environmental education and ESD, for example in the ways instruction is organised by teachers and pupils. Second, research on innovation analyses strategies for implementing environmental education and ESD in the school system, while third, research on teaching and learning examines the effects of teaching and learning processes. In describing the state of the art, longitudinal research providing evidence on the development from environmental education to ESD is examined, as are teachers’ understandings of the new concept. The results of innovation and teaching‐learning research allow us to identify research gaps and challenges, and to make recommendations for future research.